Muslims in South Korea: The way of life / Mahsuri Khalid ... [et al.] - Khalid, Mahsuri; Mohd Khir, Nurauni Aqilah; Mazlan, Nur Nabila; Mahamad Halid, Nur Farhanah; Jamal, Noraini (2017)
The purpose of this study is to understand the life of Muslims in South Korea. It focuses on cultural and societal factors that may influence the quality of life of Muslims in South Korea. This study uses an interview with 25 respondents that represent both local Muslim Koreans and Muslim foreigners who live in South Korea. The data then has been analysed as a descriptive method that shows life as Muslims in Korea is quite challenging as they are still a minority and struggling with the Islamophobia issues. The findings may be useful to any social researches in identifying more variables and factors in shaping the roles that can be played by the Muslims community in South Korea.